Handbook of Cutaneous Melanoma: A Guide to Diagnosis and Treatment - Schadendorf, Dirk (SpringerLink Bücher, 2013)
Handbook of Cutaneous Melanoma is a concise review, which discusses epidemiology, pathogenesis, clinical features, diagnosis and staging, and current and emerging treatments for local and metastatic disease. The Handbook is heavily illustrated with diagnostic guides and treatment algorithms from Dr Schadendorf (which are supported by national and international guidelines), as well as numerous images from his practice to support the text. Busy healthcare professionals who want a quick review of diagnostic and staging guidelines as well as a summary of current therapies for cutaneous melanoma will benefit from this succinct guide